1994
DOI: 10.1182/blood.v84.5.1492.bloodjournal8451492
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant adeno-associated virus-mediated gene transfer into hematopoietic progenitor cells [published erratum appears in Blood 1995 Feb 1;85(3):862]

Abstract: Recombinant adeno-associated viruses (rAAV) containing only the inverted terminal repeats (ITR) from the wild-type virus are capable of stable integration into the host cell genome, and expression of inserted genes in cultured cells. We have now defined the ability of rAAV to introduce genes into primary hematopoietic progenitors. A vector was constructed containing the coding sequences for beta- galactosidase (beta-gal), including a nuclear localization signal, under the control of a strong viral promotor. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
1

Year Published

1994
1994
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 28 publications
2
45
0
1
Order By: Relevance
“…AAV has been shown in various studies to be an effective gene delivery vector for both immortalized tissue culture cells as well as primary hematopoietic cells [15][16][17][18][19][20][21][22][23][24][25][26]. We recently showed that it is possible to successfully transduce, with chromosomal integration, the granulocyte macrophage-colony stimulating factor (GM-CSF) gene into monocytes (Mo) and DC via AAV [15].…”
Section: Introductionmentioning
confidence: 99%
“…AAV has been shown in various studies to be an effective gene delivery vector for both immortalized tissue culture cells as well as primary hematopoietic cells [15][16][17][18][19][20][21][22][23][24][25][26]. We recently showed that it is possible to successfully transduce, with chromosomal integration, the granulocyte macrophage-colony stimulating factor (GM-CSF) gene into monocytes (Mo) and DC via AAV [15].…”
Section: Introductionmentioning
confidence: 99%
“…AAV vectors have been proposed as an alternative to retroviral vectors for achieving efficient transduction of non-dividing cells [12]. However, the efficiency of integration of such vectors in hematopoietic cells is low despite the prolonged episomal persistence of rAAV [13]. Our data also suggest a transient integration or prolonged episomal expression of the transgene.…”
Section: Discussionmentioning
confidence: 63%
“…There is some evidence that AAV infection and even genomic integration may be independent of active cell cycling [67]. Wild-type AAV may preferentially integrate into a specific site on chromosome 19 and thus might have a lower chance of random insertional mutagenesis, although there is no evidence that recombinant vectors share this property [68,69). The host range of AAV is broad (human, monkey, mouse, etc.…”
Section: Adeno-associated Virusmentioning
confidence: 99%
“…Even drug resistance does not prove integration. Another group reported that 60-70% of human or rhesus CD34' cells exposed to rAAV carrying the P-galactosidase gene expressed the gene product in the nucleus [69]. Colonies grown from these cells were picked and estimated to have viral-associated DNA sequences at a copy number of one to two per cell by semi-quantitative PCR, implying but not proving integration.…”
Section: Preclinical Datamentioning
confidence: 99%
See 1 more Smart Citation